Role of Copper in the Onset of Alzheimer’s Disease Compared to Other Metals - Bagheri, Soghra; Squitti, Rosanna; Haertlé, Thomas; Siotto, Mariacristina; Saboury, Ali A. (Frontiers in Aging Neuroscience, 2018)
Alzheimer’s disease (AD) is a neurodegenerative disorder that is characterized by amyloid plaques in patients’ brain tissue. The plaques are mainly made of β-amyloid peptides and trace elements including Zn2+, Cu2+, and Fe2+. Some studies have shown that AD can be considered a type of metal dyshomeostasis. Among metal ions involved in plaques, numerous studies have focused on copper ions, which seem to be one of the main cationic elements in plaque formation. The involvement of copper in AD is controversial, as some studies show a copper deficiency in AD, and consequently a need to enhance copper levels, while other data point to copper overload and therefore a need to reduce copper levels. In this paper, the role of copper ions in AD and some contradictory reports are reviewed and discussed.